Awareness of predatory publishing for Peruvian university professors and lecturers doing research - Sotomayor-Beltran, Carlos (2020)
Predatory open access journals and predatory conferences’ main purpose is to make profit rather than promoting good science. In Peru, the University Law 30220 asks that professors and lecturers undertake research duties at universities. Hence, nowadays part of this academic staff is required to write scientific articles. However, not all of them are experienced on how to write a scholarly paper. Thus, in the rush to comply with the publication requirements that their individual institutions demand from them, a great number of these professors and lecturers are likely to fall prey of predatory publishing, which already is happening in other developing nations. This publishing method is not only unethical because it produces low-quality articles but also is an egregious mismanagement of the resources that universities allocate to fund research. Moreover, the time and effort that the academic staff put to the production of low-quality papers also completely go to waste. Professors and lecturers who follow these bad practices should be penalized; this also avoids the emergence of fraudulent research authorities. Thus, vice-rectorates for research in Peruvian universities should take corrective or preventive measures to promote the production of high-quality papers by part of their academic staff.